2018
DOI: 10.1002/jor.24132
|View full text |Cite
|
Sign up to set email alerts
|

In‐vivo elongation of anterior and posterior cruciate ligament in bi‐cruciate retaining total knee arthroplasty

Abstract: Anterior and posterior cruciate ligament (ACL and PCL) sacrifice in contemporary total knee arthroplasty (TKA) has been considered a potential factor leading to abnormal knee kinematics. Bi-cruciate retaining (BCR) TKA design allows retention of both ACL and PCL. However, there is a limited data on the ACL/PCL in-vivo elongation characteristics of BCR TKA. The study aimed to evaluate and compare the in-vivo elongation patterns of ACL/PCL between BCR TKA and contralateral non-implanted knee and to explore poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 47 publications
2
22
0
Order By: Relevance
“…12 In addition, Tsai et al have reported overstretching of the PCL in BCR-TKA knees. 10 Higher ACL tension of knees after The Journal of Knee Surgery BCR-TKA may prevent posterior femoral rollback. Furthermore, in normal knee kinematics, a lateral pivot pattern was observed from early-flexion to mid-flexion during cross-leg.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…12 In addition, Tsai et al have reported overstretching of the PCL in BCR-TKA knees. 10 Higher ACL tension of knees after The Journal of Knee Surgery BCR-TKA may prevent posterior femoral rollback. Furthermore, in normal knee kinematics, a lateral pivot pattern was observed from early-flexion to mid-flexion during cross-leg.…”
Section: Figmentioning
confidence: 99%
“…[7][8][9] Tsai et al reported that BCR-TKA did not fully restore the cruciate ligament elongation patterns and anteroposterior stability of normal knees. 10 Moreover, several studies have demonstrated that the kinematics of knees that underwent BCR-TKA differed from that of normal knees during passive flexion, passive extension, sit-to-stand exercises, deep lunges, and stair climbing. [11][12][13] Arauz et al reported that these kinematic differences between BCR-TKA knees and normal knees might be attributed to the articular surface.…”
mentioning
confidence: 99%
“…15 A recent in vivo study investigated ACL elongation patterns during sit-to-stand (STS), demonstrating that BCR TKA did not fully restore healthy knee ACL elongation patterns. 16 In addition, this study suggested that joint gap changes are significantly correlated with alterations in ACL elongation patterns. Although recent studies indicated that surgical technique is important for patient outcomes, 11,12 there is limited studies assessing the potential effect of implant alignment on ACL elongation patterns.…”
mentioning
confidence: 62%
“…Nevertheless, the accuracy of this validated approach has been demonstrated in the literature and thus this method has been implemented in a variety of studies in the literature. 16,31 Second, although all patients had morphologically intact cruciate ligaments, there may be degenerative histological changes, which may affect in vivo cruciate ligament function. Several studies have reported histological degeneration in macroscopically normal cruciate ligaments in osteoarthritic knees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation